IMPLIKASI TUMPANG TINDIH KEWENANGAN DALAM PERIZINAN USAHA (STUDI KASUS DI KECAMATAN TENAYAN RAYA KOTA PEKANBARU TAHUN 2013-2014) - Riandy Wendra; Auradian Marta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The research present describe the implication of dualism authority in business licensing (study case in Tenayan Raya District Pekanbaru City in 2013-2014). The dualism authority in licencing in Pekanbaru City was held by Head of District, Industrialization and Trading Agency and Integrated Licensing Service Board in Pekanbaru City, then it make effect for society when doing a licensing.The research use the methode are qualitative methodes that analyze problem research by describe the subject and object conditions based on real fact. This research use location in Pekanbaru City and researcher collect data from books, government regulation, jurnal, mass media, website and deep interview with informan research likes Asistent of Government Pekanbaru, House of Representative Pekanbaru City, Head of Section in Integrated Licensing Service Board Pekanbaru City, and Head of Section in Tenayan Raya District.The conclusion of this research are the factors impeding the dualism authority business licensing in Tenayan Raya District Pekanbaru City cause the dualism authority between Integrated Licensing Service Board Pekanbaru City and Head of District to create a licensing. And the implication of dualism authority in business licensing in Tenayan Raya District Pekanbaru City are communication and coordination between stake holder, the confused and awarness of in create a business licensing especially in Tenayan Raya District Pekanbaru City.Keywords: implication, dualism, authority and licensing.